CHARACTERISTICS AND RISK FACTORS OF BREAST CANCER AT THE CENTRAL GENERAL HOSPITAL PROF. DR. I G.N.G. NGOERAH IN 2022 - Aqilah, Nadya Zalfa; Wetan, Ni Gusti Ayu Agung Manik Yuniawaty; Setiawan, I Gede Budhi; Adiputra, Putu Anda Tusta (E-Jurnal Medika Udayana, 2024)
Breast cancer is a disease that has high mortality in women throughout the world. Breast cancer has characteristics and risk factors that influence the incidence of breast cancer. The research method uses a retrospective descriptive study and uses secondary data, namely medical records at the Central General Hospital Prof. Dr. I G.N.G. Ngoerah in 2022. Of the total 551 samples, only 319 samples had complete medical records. The variables studied were age, clinical stage, histopathological type, biopsy grade, subtype, lesion location, menopausal status, age at menarche, age at menopause, family history of cancer, parity, breastfeeding history, history of hormonal therapy, and nutritional status in terms of BMI. The results showed that of the 319 breast cancer patients, 77.4% were ?45 years old, 38.2% were stage IIIB, 86.2% were invasive ductal carcinoma, 56.4% were grade III, 36.4% were luminal B subtype, 41.4% were in the menopausal phase, the average age of menarche was 13 years old, 42% had menopause in the 45-50 year age range, 4.4% had a family history of cancer, 73% were multiparous, 91.5% had a history of breastfeeding, 23.8% had a history of hormonal therapy, and 37.3% had a normal BMI nutritional status. Keywords: Characteristics, Risk Factors, Breast Cancer